2004
DOI: 10.1111/j.1365-2591.2004.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

FT‐Raman spectroscopy of calcium hydroxide medicament in root canals

Abstract: Calcium hydroxide medicament in root canals became transformed into calcium carbonate in the apical region within 2 days. Although the transformation continued with time, approximately 90% of the calcium hydroxide remained unchanged after 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
1
23
0
2
Order By: Relevance
“…This material has a very low solubility, creates only a mildly alkaline pH of 8.0, and as a result has neither biological nor antibacterial properties. 52 Kwon et al 52 showed that 10 per cent of the calcium hydroxide was converted to calcium carbonate in the apical region within two days and the remainder was unchanged after six weeks. Little calcium carbonate was detected in samples from the middle portion of the root canal even after six weeks.…”
Section: (A) Calcium Hydroxidementioning
confidence: 99%
“…This material has a very low solubility, creates only a mildly alkaline pH of 8.0, and as a result has neither biological nor antibacterial properties. 52 Kwon et al 52 showed that 10 per cent of the calcium hydroxide was converted to calcium carbonate in the apical region within two days and the remainder was unchanged after six weeks. Little calcium carbonate was detected in samples from the middle portion of the root canal even after six weeks.…”
Section: (A) Calcium Hydroxidementioning
confidence: 99%
“…803 cm -1 (1163 nm) and 726 cm -1 (1153 nm). As mentioned above, the same bands were also recognized in the corresponding spectra of some synthetic belites (C 2 S), however, two different specimens of C 2 S have shown different positions in spectra [19]. Although our studies of that group of materials are not focused on providing an explanation of the origin of the fluorescence emission excited by NIR laser radiation, they add nevertheless some arguments for further discussion on that issue.…”
Section: Discussionmentioning
confidence: 62%
“…No other bands have been found by them, when Ca(OH) 2 is excited with the laser line of 1064 nm. Spectrum of calcium hydroxide medicament reported by Kwon et al [19], apart from two strong bands at 796 and 721 cm -1 , showed a broad band of low intensity centred at 930 cm -1 and a very weak feature at 363 cm -1 .…”
Section: Lime Bindersmentioning
confidence: 94%
See 1 more Smart Citation
“…O hidróxido de cálcio em contato com o CO 2 (dióxido de carbono), submete-se também à mudança química, sendo transformado no carbonato de cálcio 14 . Alguns pesquisadores analisaram a perda na qualidade do produto em conseqüência de sua carbonação devido ao gás do dióxido de carbono na atmosfera 11,12 .…”
Section: Resultsunclassified